Advanced Placement: The Dual Challenge of Equal Access and Effectiveness. (October 2018) - Kolluri, Suneal
The Advanced Placement (AP) program offers an opportunity for students to earn college credit and develop college-ready skills in high school. The curriculum was initially designed for "superior" students at exclusive private schools. Recently, however, the AP program has expanded to serve more students from marginalized backgrounds, and equitable access has become one of its core objectives. Scholars have questioned whether AP can continue to offer effective college preparation while expanding beyond the populations it was initially designed to serve. This literature review summarizes existing research on whether the AP program has achieved its dual goals of equal access and effectiveness. The extant literature suggests that, despite impressive gains in access to AP, significant barriers remain to its becoming a program that ensures equal access for all students and effectively prepares them for college coursework. Assessing whether these barriers can be overcome, however, demands new approaches to AP research.